Pengaruh Implementasi Kedwibahasaan terhadap Kemampuan Kognitif dalam Keterampilan Menulis - Zakia Nur Huda; Salma Nur Fadilah; Ichsan Fauzi Rachman (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Writing skills are an important aspect in developing a person's communication skills. However, the writing process does not only involve linguistic aspects, but also deep cognitive aspects. One factor that is often overlooked but has a significant influence on writing ability is bilingualism. This article aims to explore the influence of bilingualism on cognitive abilities in writing skills. This study uses a qualitative descriptive method through data analysis through a literature review of relevant previous research regarding the influence of bilingualism on cognitive abilities in writing skills. The study results show that there is a strong relationship between bilingualism and cognitive abilities in writing skills. Someone who is strong bilingual tends to show better cognitive abilities in building arguments, organizing ideas, and organizing information effectively in their writing. In addition, awareness of language structure and wider vocabulary is also a characteristic of participants who are good bilinguals. These findings provide in-depth experience regarding the role of bilingualism in the development of writing skills, as well as its implications in the context of education and language learning.